Assessment of the potential risk of oteseconazole and two other tetrazole antifungals to inhibit adrenal steroidogenesis and peripheral metabolism of corticosteroids - Jäger, Marie-Christin; González-Ruiz, Víctor; Joos, Friedrich L.; Winter, Denise V.; Boccard, Julien; Degenhardt, Thorsten; Brand, Steve; Rudaz, Serge; Thompson, George R.; Odermatt, Alex (Frontiers in Pharmacology, 2024)
The triazole antifungals posaconazole and itraconazole can cause pseudohyperaldosteronism with hypertension and hypokalemia, edema, and gynecomastia by inhibiting steroid synthesis and metabolism. Mechanisms underlying pseudohyperaldosteronism include inhibition of adrenal 11β-hydroxylase cytochrome-P450 (CYP) 11B1 and 17α-hydroxylase (CYP17A1) as well as peripherally expressed 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2). To enhance specificity for fungal CYP51, tetrazoles have been developed. This study employed H295R adrenocortical cells and enzyme activity assays to assess the potential risk of oteseconazole and two other tetrazoles, VT-1598 and quilseconazole, to inhibit adrenal steroidogenesis or 11β-HSD2. Steroidomic footprint analyses of H295R cell supernatants using untargeted liquid-chromatography-high-resolution mass-spectrometry (LC-HRMS) indicated overall patterns common to oteseconazole, quilseconazole and itraconazole, as well as similarities between VT-1598 and isavuconazole. Additionally, more specific features of the steroid signatures were observed. Targeted quantification of nine adrenal steroids in supernatants from treated H295R cells revealed an overall inhibition of adrenal steroidogenesis by the three tetrazoles, itraconazole and isavuconazole, providing an explanation for their similar steroidomic pattern. Applying recombinant enzymes indicated that this effect is not due to direct inhibition of steroidogenic enzymes because no or only weak inhibition could be observed. Moreover, oteseconazole and the two other tetrazoles did not inhibit 11β-HSD2, suggesting that they do not pose a risk of pseudohyperaldosteronism. Furthermore, oteseconazole did not alter steroid concentrations in a recent clinical study. Nevertheless, follow-up studies should assess the mechanism underlying the observed overall steroidogenesis inhibition by tetrazoles, itraconazole and isavuconazole, and whether concentrations achievable in a subgroup of susceptible patients might cause adrenal insufficiency and hyperplasia.